Sinus Venosus Atrial Septal Defect Complicated by Eisenmenger Syndrome and the Role of Vasodilator Therapy - Amornpol Anuwatworn; Maheedhar Gedela; Edgard Bendaly; Julia A. Prescott-Focht; Jimmy Yee; Richard Clark; Orvar Jonsson (Case Reports in Cardiology)
Sinus venosus atrial septal defect is a rare congenital, interatrial communication defect at the junction of the right atrium and the vena cava. It accounts for 5–10% of cases of all atrial septal defects. Due to the rare prevalence and anatomical complexity, diagnosing sinus venous atrial septal defects poses clinical challenges which may delay diagnosis and treatment. Advanced cardiac imaging studies are useful tools to diagnose this clinical entity and to delineate the anatomy and any associated communications. Surgical correction of the anomaly is the primary treatment. We discuss a 43-year-old Hispanic female patient who presented with dyspnea and hypoxia following a laparoscopic myomectomy. She had been diagnosed with peripartum cardiomyopathy nine years ago at another hospital. Transesophageal echocardiography and computed tomographic angiography of the chest confirmed a diagnosis of sinus venosus atrial septal defect. She was also found to have pulmonary arterial hypertension and Eisenmenger syndrome. During a hemodynamic study, she responded to vasodilator and she was treated with Ambrisentan and Tadalafil. After six months, her symptoms improved and her pulmonary arterial hypertension decreased. We also observed progressive reversal of the right-to-left shunt. This case illustrates the potential benefit of vasodilator therapy in reversing Eisenmenger physiology, which may lead to surgical repair of the atrial septal defect as the primary treatment.